Athar ‘Ulūm al-Lughah al-‘Arabīyah fī Fahm al-Nuṣūṣ al-Shar‘īyah: Muqaddimah Tanẓīrīyah Ūlá - Ra'id Ali al-Kurdi; Rim Farhan al-Mu'ayitah; Umar 'Abd Alllah al-Fajjawi (Al-Ma‘rifah, 2018)
In the ancient centuries of Arabic and Islamic heritage, all sciences were connected and the benefit was exchanged among them. However, the stsudents received information from scholars by listening to their lectures, sessions and presentations, and then they became qualified with certificates in era's sciences which assisted them in their fields, by delivering questions and solving problematic and controversial issues. This paper deals with the impact of Arabic language's sciences on understanding the Islamic contexts. It has divided into two tracks, first: shine examples and models from Arabic and Islamic heritage which explain the interesting of commentators and jurists in Arabic sciences, like Ibn Abbas, Ashshafie, Attabari and Azzamakhshari. Second: examples of linguistics understanding in some of The Holy Quran's verses and its impact on assisting commentators and jurists in formulating their rules.